Using Trolls and Bots in Social Media: Propagandistic Influence on Public Opinion: A Literature Review - Salome Khazhomia (European Scientific Journal, ESJ, 2025)
In recent years, the spread of various forms of misinformation, including fake news, rumors, and conspiracy theories, has increased. One of the primary ways misinformation spreads is through trolls and bots. Trolls are real users, while bots are automated, but both influence society in similar ways. However, they differ in the degree of harm they cause-some are highly damaging, while others have a lesser impact. One significant use of these entities is in propaganda. This paper focuses on analyzing propaganda theories in relation to society and its behaviors. Media has become a focal point in propaganda theories, as theorists have examined the influence of media content on society. The study aims to determine the impact of fake accounts on social media and explore strategies for managing trolls and bots. Key research areas include understanding how misinformation spreads, how people perceive it, and how detection methods can be improved. The relevance of this research stems from the expansive nature of social media, which serves as a vehicle for propagandistic tactics employed by trolls and bots. The study adopts a qualitative research approach, relying primarily on literature review and theoretical analysis. It draws upon existing research, theories, and findings to build its argument, referencing various studies on misinformation, fake accounts, propaganda theories, and the role of bots and trolls in media manipulation. To provide a strong theoretical framework, the study incorporates theories such as Lasswell’s propaganda theory, modern propaganda theories, and the theory of informational autocracy. Additionally, it discusses previous studies on misinformation, including research on disinformation detection, cognitive biases, and propaganda’s effects on public opinion.